Synthesis and Alkali‐Metal‐Ion Complexation of P‐Stereogenic Diphosphacrowns. Issue 4 (2nd June 2016) - Morisaki, Yasuhiro; Kato, Ryosuke; Chujo, Yoshiki
Abstract: Phosphine is conformationally stable because of the high inversion energy barrier of the phosphorus atom, which allows the phosphorus atom to become a chiral center. Thus, enantiopure P‐stereogenic 12‐, 15‐, 18‐, and 21‐membered aliphatic phosphines "diphosphacrowns" were synthesized from secondary P‐stereogenic bisphosphine as a chiral building block. Their complexation behaviors with alkali metal ions are investigated in comparison with benzo‐18‐diphosphacrown‐6 and benzo‐18‐crown‐6. 15‐, 18‐, and 21‐Membered diphosphacrowns captured alkali metal ions to form 1:1 metal complexes. Unique guest selectivity was observed, as diphosphacrowns encapsulated smaller alkali metal ions than common crown ethers; for example, 18‐membered diphosphacrowns interacted more strongly with Na + than K + . The difference in guest selectivity between diphosphacrowns and common crown ethers is speculated to result from the cavity size, owing to the large phosphorus atom as well as steric hindrance around the phosphine moiety. Abstract : Crown a new winner : The synthesis of enantiopure aliphatic diphosphacrowns with 12‐, 15‐, 18‐, and 21‐membered rings from P‐stereogenic secondary bisphosphines is reported. The complexation of alkali metal ions is disclosed, in addition to that of benzo‐18‐diphosphacrown‐6 and benzo‐18‐crown‐6. Diphosphacrowns selectively form a 1:1 complex with smaller alkali metal ions, as compared to the common crown ethers; for example, 18‐diphosphacrown‐6 prefers Na + to K + .